ISLAMIC EDUCATION AND LIBERATION FROM FEUDALISM - Syaiful Anwar (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2018)
This article aimed at describing Islamic Education strategies and functions in liberating humankind from feudalism. Islam Believes that everybody’s status is equal, one thing that makes him different is his piety. There are Three harmonious relationships can be identified; those are the relationship between human being and God “Allah SWT” (Habblun min Allah, theological aspect), between human being and other human being (Hablun min al-nas, athropo-sociological aspect), and between human being and the natural environment (Hablun min al-‘alam, cosmological aspect). These harmonious relationships are the manifestation of perfect faithfulness of a Muslim to Allah SWT.In the religious dimension, the main purpose of Islam is to develop awareness and understanding about the meaning and of human’s life in relation to God. Meanwhile, in terms of social dimension, the purpose of Islamic Education is to develop understanding of harmonious relationship, either between human beings or between human being with the environment. In this context, human beings hold the responsibility for restraining a society from obstinacy, inanity, and anarchism. In this respect, the concept of liberalism in Islamic Education is to place teachers and students in a harmonious relationship. This relationship is to create learning atmosphere which is based on the principle of democratic and two-way relationship.